Development of an oral cancer recurrence mouse model after surgical resection - Behren, Andreas; Kamenisch, York; Muehlen, Sabrina; Flechtenmacher, Christa; Haberkorn, Uwe; Hilber, Hermann; Myers, Jeffrey; Bergmann, Zazie Philippine; Plinkert, Peter K.; Simon, Christian (International journal of oncology, 2010)
Oral squamous cell carcinomas (OSCC) are frequent epithelial malignancies and afflicted with a poor prognosis. The majority of these cancers are treated with surgical resection and local recurrences are predominantly responsible for a fatal outcome. In order to provide a better understanding of the development of these local recurrences after surgical ablation, we developed an orthotopic floor-of-mouth squamous cell carcinoma murine model, in which local recurrences occur at a high frequency (55%, 8 out of 15 mice) within 6-21 days after microsurgical removal of the primary. Expression of the enhanced green fluorescent protein (eGFP) in the cancer cells allows in this new model to confirm complete surgical resection under the microscope and helps to track repopulating primary tumor cells in the local recurrence by optical imaging. In addition the model resembles all typical features of invasive head and neck cancers including the formation of lymph node metastasis and local infiltration.
Gesehen am 05.01.2023